A New Method for Time-Jerk Optimal Trajectory Planning Under Kino-dynamic Constraint of Robot Manipulators in Pick-and-Place Operations - Bendali Nadir; Ouali Mohammed; Kifouche Abdessalam (Institute of Advanced Engineering and Science, 2014)
A new method for time-jerk optimal planning under Kino-dynamic constraints of robot manipulators in pick-and-place operations is described in this paper. In order to ensure that the resulting trajectory is smooth enough, a cost function containing a term proportional to the integral of the squared jerk (defined as the derivative of the acceleration) along the trajectory is considered. Moreover, a second term, proportional to the total execution time, is added to the expression of the cost function. A Cubic Spline functions are then used to compose overall trajectory. This method makes it possible to deal with the kinematic constraints as well as the dynamic constraints imposed on the robot manipulator. The algorithm has been tested in simulation yielding good results.